Comparison of hepatic arterial infusion chemotherapy versus sorafenib monotherapy in patients with advanced hepatocellular carcinoma. Issue 9 (September 2015) - Kawaoka, Tomokazu; Aikata, Hiroshi; Hyogo, Hideyuki; Morio, Reona; Morio, Kei; Hatooka, Masahiro; Fukuhara, Takayuki; Kobayashi, Tomoki; Naeshiro, Noriaki; Miyaki, Daisuke; Hiramatsu, Akira; Imamura, Michio; et al.
<x xml:space="preserve">Abstract</x> Objectives Sorafenib is the standard treatment for advanced hepatocellular carcinoma (HCC) with distant metastasis, unresectable HCC, and those refractory to transcatheter arterial chemoembolization (TACE) or with macroscopic vascular invasion (MVI). The application of sorafenib has been approved by the Japanese Government‐sponsored Medicare for unresectable HCC. In this retrospective cohort study we aimed to compare various aspects of HAIC with sorafenib in the treatment of Child–Pugh A patients with advanced HCC who were otherwise free of extrahepatic metastasis. Methods Altogether 177 patients with advanced HCC at Child–Pugh class A who were free of extrahepatic metastasis were retrospectively enrolled. The patients were divided into the HAIC group (n = 136) and the sorafenib group (n = 41), and were followed up until their death or withdrawal of therapy. Responses to treatment and overall survival were determined and compared between the two groups. Results The proportion of patients with complete response, partial response, stable disease and progressive disease were 5.9%, 25.0%, 40.4% and 21.3% in the HAIC and 2.4%, 2.4%, 43.9% and 41.5% in the sorafenib group, respectively. The response rate was higher in the HAIC group than in the sorafenib group (30.9% vs 4.8%). The median survival time was 10 months in both HAIC and sorafenib groups. In patients with macroscopic vascular invasion (MVI) by the case‐control method, the response rate was higher in the HAIC group than in the sorafenib group. Overall survival was longer in the HAIC group than in the sorafenib group (14 months vs 7 months, P = 0.005). Multivariate analysis identified MVI (hazard ratio 2.4, P = 0.018) as an independent prognostic factor of survival in the sorafenib group. Conclusions Response rate to HAIC was higher than that to sorafenib monotherapy. Prognosis was favorable in HAIC responders despite MVI. HAIC might be a potential treatment option for advanced HCC without extrahepatic metastasis.